Two-port laparoscopic management of a giant pseudocyst complicating ventriculoperitoneal shunt - Sandesh V Parelkar; Beejal V Sanghvi; Devdas S Samala; Bhupesh A Paradkar; Shalil H Patil; Sanjay N Oak (Wolters Kluwer Medknow Publications, 2014)
Insertion of a ventriculo-peritoneal (VP) shunt is the most common operative procedure for the treatment of hydrocephalus in children. Of the several causes of shunt malfunction, cerebrospinal fluid (CSF) pseudocyst is relatively uncommon. There are several modalities to treat a CSF pseudocyst. Laparotomy is required, at times, more than once. We managed a patient of CSF pseudocyst with two-port laparoscopy, by deroofing the psuedocyst and repositioning of the shunt. This minimally invasive technique avoids morbidity associated with laparotomy and aids in early recovery.